Cytokine associated with severity of depressive symptoms in female nurses in Korea - Kim, Yoonjoo; Pang, Yanghee; Park, Hyunki; Kim, Oksoo; Lee, Hyangkyu (Frontiers in Public Health, 2023)
Background Depression has been associated with the risk of developing physical illnesses and diseases. Inflammatory hypotheses of immunoactive and dysregulated cytokine production have been proposed to describe this association; however, data pertaining to the high prevalence of depression among nurses are limited. Objective This study aimed to use a comprehensive immune-profiling approach to determine whether an abnormal profile of circulating cytokines could be identified in nurses with self-reported depression and whether this profile is associated with the severity of depression. Methods We investigated a cohort of 157 female nurses in Korea. The self-report Patient Health Questionnaire was used to measure the depression levels of nurses. In addition, peripheral blood samples were collected and used to measure the cytokine profile using the Luminex multiplexing system. Generalized gamma regression analyses were conducted to evaluate the association between cytokine and depressive symptoms. Results Regarding severity of depressive symptoms, 28.0% of nurses had moderately severe depression while 9.6% had severe depression. Moderately-severe depressive symptoms in nurses were associated with elevated levels of interleukin-6 (B = 0.460, p = 0.003), interleukin-8 (B = 0.273, p = 0.001), and interleukin-18 (B = 0.236, p = 0.023), whereas interferon-gamma levels (B = −0.585, p = 0.003) showed the opposite profile. Participants with severe depressive symptoms presented decreased interferon-gamma levels (B = −1.254, p < 0.001). Conclusion This study demonstrated that proinflammatory cytokines were associated with depression among nurses. This calls for early detection and intervention, considering the mechanisms linking depression to physical illness and disease.